Fashionable sebagai Sumber Ide Penciptaan Karya Seni Grafis - Nurhaslina, Siti; Ariusmedi, Ariusmedi (Al-DYAS, 2023)
The purpose of making this work is to visualize the negative impact of fashionable so that people know about the current trends that affect a person's life a lot in the form of graphic artwork u sing the Stencil Print technique. The creation method in this final work is carried out in stages, starting from the preparation stage, the elaboration stage, the synthesis stage, then the realization of the concept and finally the completion or finishing stage of the work. Ten works of graphic art using the stencil print method with a size of 50 x 40 cm with the titles "Obsession", "Beauty", "Addiction", "Wrong Direction", "Sacrifice", "Shouldn't", "Royal", " Free association”, “Aggression”, ”Update.